Parambassis bistigmata, a new species of glassperch from north-eastern India (Teleostei: Ambassidae) - Geetakumari, Khangjrakpam (Zootaxa, 2012)
Parambassis bistigmata, a new species of glassperch from northeast India, is distinguished from its congeners by the com-bination of the following characters: two distinct black spots on either side of the anal-fin origin connected by a narrowblack curved line; 13–14 gill rakers on the first gill arch; 65–67 scales in lateral series; a well developed pre-orbital edgewith prominent, acute spines, almost covering the upper lip; dorsal and ventral sides of caudal peduncle with a longitudinal black stripe; and the presence of a faint, vertically elongated humeral spot.